Question
upstudy study bank question image url

Write a polynomial with the following given zeros (roots): \( -2,-3,4-3 i \)

Ask by Stuart Ramirez. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The polynomial with zeros –2, –3, and 4 – 3i is \( P(x) = x^4 - 3x^3 - 9x^2 + 77x + 150 \).

Solution

We are given the zeros –2, –3, and 4 – 3i. Since we want a polynomial with real coefficients, we must include the complex conjugate of 4 – 3i, which is 4 + 3i, as a zero. Step 1. Write the linear factors corresponding to each zero:   Factor 1: (x + 2)   Factor 2: (x + 3)   Factor 3: (x – (4 – 3i))  = (x – 4 + 3i)   Factor 4: (x – (4 + 3i))  = (x – 4 – 3i) Step 2. Multiply the complex conjugate factors first:   (x – 4 + 3i)(x – 4 – 3i) This product is of the form (a + b)(a – b) = a² – b², where a = x – 4 and b = 3i. Thus,   = (x – 4)² – (3i)²   = (x – 4)² – (–9)    [since (3i)² = –9]   = (x – 4)² + 9 Expanding (x – 4)²:   = x² – 8x + 16 + 9   = x² – 8x + 25 Step 3. Now multiply with the remaining factors (x + 2) and (x + 3). First, combine them:   (x + 2)(x + 3) = x² + 5x + 6 Step 4. Multiply the quadratic factors:   (x² + 5x + 6)(x² – 8x + 25)   Performing the multiplication:    x²·x² = x⁴    x²·(–8x) = –8x³    x²·25 = 25x²    5x·x² = 5x³    5x·(–8x) = –40x²    5x·25 = 125x    6·x² = 6x²    6·(–8x) = –48x    6·25 = 150 Now, combine like terms:   x⁴ term: x⁴   x³ terms: (–8x³ + 5x³) = –3x³   x² terms: (25x² – 40x² + 6x²) = –9x²   x terms: (125x – 48x) = 77x   Constant: 150 Thus, the polynomial is:   P(x) = x⁴ – 3x³ – 9x² + 77x + 150 This is a monic polynomial with the given zeros.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To construct a polynomial with the given roots \( -2, -3, \) and \( 4 - 3i \), we first note that complex roots occur in conjugate pairs. Therefore, the conjugate \( 4 + 3i \) is also a root. The polynomial can be expressed as: \[ P(x) = (x + 2)(x + 3)(x - (4 - 3i))(x - (4 + 3i)) \] Now, simplifying the complex pair: \[ (x - (4 - 3i))(x - (4 + 3i)) = ((x - 4) + 3i)((x - 4) - 3i) = (x - 4)^2 + 9 \] Expanding it gives: \[ (x - 4)^2 + 9 = x^2 - 8x + 16 + 9 = x^2 - 8x + 25 \] Now putting it all together: \[ P(x) = (x + 2)(x + 3)(x^2 - 8x + 25) \] We can multiply out the first two factors: \[ (x + 2)(x + 3) = x^2 + 5x + 6 \] Now the polynomial becomes: \[ P(x) = (x^2 + 5x + 6)(x^2 - 8x + 25) \] Next, we expand this: 1. \( x^2 \cdot (x^2 - 8x + 25) = x^4 - 8x^3 + 25x^2 \) 2. \( 5x \cdot (x^2 - 8x + 25) = 5x^3 - 40x^2 + 125x \) 3. \( 6 \cdot (x^2 - 8x + 25) = 6x^2 - 48x + 150 \) Combining these, we find: \[ P(x) = x^4 - 3x^3 + 81x^2 + 125x + 150 \] So the polynomial with the given roots is: \[ P(x) = x^4 - 3x^3 + 81x^2 + 125x + 150 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy